Social Media Engagement, Mental Health and Physical Health of Employed Late Adolescents: Basis for a Digital Wellness Awareness Program - Jobelle Resuello; Alwyn H. Delfinado; Concepcion D. Alcantara; Danielle Faye A. Tobias; Christian B. Villapando (International Journal of Innovative Science and Research Technology, 2026)
For late adolescents, especially those who are already employed, social media use has grown to be an integral part of their everyday lives. Social media platforms offer chances for social connection, communication, and information sharing, but excessive or unhealthy use can have negative effects on people's physical and mental well-being. The purpose of this study was to evaluate the connection between late-adolescent employed people's use of social media, mental health, and physical health. It specifically aimed to determine the respondents' degree of social media use and investigate its relationship to their physical and mental health conditions. This study used a descriptive-correlational research design with a quantitative research methodology. A structured survey questionnaire measuring social media engagement, mental health indicators, and experiences related to physical health was used to collect data from working late adolescents. To find trends, connections, and important correlations between the variables, the gathered data was examined using the proper statistical software. The study's conclusions should help us better understand how social media use impacts late adolescents who are employed in terms of their general well-being. The findings could be used as a foundation for creating a Digital Wellness Awareness Program that supports the enhancement of young workers' mental and physical health, encourages responsible social media use, and supports healthy online behaviors. Educators, employers, mental health advocates, and future researchers may find this study useful in developing interventions that tackle the problems related to excessive social media use.